ANALYSIS OF EFFECTIVENESS ASSESSMENT CRITERIA OF FREE ECONOMIC ZONES IN DIGITAL ECONOMY CONDITIONS - Oltaev Sh.S, (TADQIQOTLAR, 2026)
Abstract:  This article  examines  the  analysis  of the  criteria  for  assessing the effectiveness  of  free  economic  zones  in  the  digital  economy.  The  development  of criteria  for  assessing  the  activities  of  free  economic  zones  serves  as  a  basis  for stimulating  their  development.  Based  on  world  experience,  it  is  important  for  the development of countries and regions to identify indicators of the effective functioning of free economic zones, pay attention to their analysis, and based on this, select the most  appropriate  methods  of  attracting  investors.  The  article  also  highlights  the importance  of  analyzing  indicators,  experiences  and  implementing  them  in  this process.